2022
DOI: 10.3390/dairy3030041
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Aflatoxin M1 in Milk and Milk Products from Punjab, Pakistan, and Estimation of Dietary Intake

Abstract: In the present study, 124 samples of milk and milk products were analyzed for the presence of aflatoxin M1 (AFM1), which were purchased from the central cities of Punjab, Pakistan. The analysis was carried out using reverse-phase liquid chromatography, which was equipped with a fluorescence detector. The results showed that 66 samples (53.8%) of raw milk and milk products were found to be contaminated with detectable levels of AFM1 above ≤50 ng/L, and 24.2% of the samples had levels of AFM1 higher than the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
3
4
0
Order By: Relevance
“…Furthermore, in some East African countries, higher occurrences of AFM1 in raw milk of dairy cows, with a contamination rate of 95.45% (N=44; mean=2.07 µg/L) in Sudan [63], prevalence of 100% (N=96; mean: 0.290.3 µg/L) in Kenya [64] and occurrence of 83.8% (N=37) in Tanzania were reported [25]. However, consistent with this finding, the prevalence rate of AFM1 of 68.42% (N=38), 64.2% (N=38), and 58.8% (N=701) in Yemen, Pakistan, and Lebanon were reported respectively [50,65,66]. Similarly, the average concentration of 0.183 µg/L (N=38), and 156.71 ng/L (N=84) of AFM1 were reported in the raw milk of dairy cows of Algeria and Yemen respectively [50,67].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Furthermore, in some East African countries, higher occurrences of AFM1 in raw milk of dairy cows, with a contamination rate of 95.45% (N=44; mean=2.07 µg/L) in Sudan [63], prevalence of 100% (N=96; mean: 0.290.3 µg/L) in Kenya [64] and occurrence of 83.8% (N=37) in Tanzania were reported [25]. However, consistent with this finding, the prevalence rate of AFM1 of 68.42% (N=38), 64.2% (N=38), and 58.8% (N=701) in Yemen, Pakistan, and Lebanon were reported respectively [50,65,66]. Similarly, the average concentration of 0.183 µg/L (N=38), and 156.71 ng/L (N=84) of AFM1 were reported in the raw milk of dairy cows of Algeria and Yemen respectively [50,67].…”
Section: Discussionsupporting
confidence: 61%
“…Likewise, 58% and 42% of milk samples from different sites of Central Highland and 96% and 82% of milk from Bishoftu town contain the concentration of AFM1 exceeding the threshold limit of ESA/EU and FDA in Ethiopia [31,62]. However, Iqbal et al [65] and Daou et al [66] reported that 25% and 28% of the milk samples exceeded the tolerable limit of ESA/EU (0.05 µg/L) of AFM1, which is relatively lower compared to the present finding.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum concentration of AFM1 (197.37 µg/L) in Tunisian raw milk was higher than that reported in other countries around the world, including Cyprus (0.017 µg/L; [ 42 ]), Turkey (0.034 µg/L; [ 43 ]), Italy (0.026 µg/kg; [ 44 ]), Pakistan (0.021 µg/L; [ 45 ]), Brazil (0.045 µg/L; [ 46 ]), China (0.036 µg/L; [ 47 ]), Lebanon (0.440 µg/L; [ 48 ]), and Spain (1.36 µg/L; [ 49 ]), and lower than that reported in Kenya (273.8 µg/L; [ 50 ]) and Iran (240 µg/L; [ 51 ]).…”
Section: Discussionmentioning
confidence: 83%
“…After consumption by lactating animals, aflatoxin B 1 is excreted as aflatoxin M 1 (AFM 1 ) in milk, potentially posing a health hazard to the consumers of milk and milk products ( Yunus et al, 2011 ; IARC, 2012 ). Studies conducted in different low and middle-income countries have invariably found milk to be frequently contaminated with AFM 1 to different extents, particularly in sub-Saharan Africa ( Lindahl et al, 2018 ; Kagera et al, 2019 ; Kemboi et al, 2020 ), and Asia ( Iqbal et al, 2022 ; Salari et al, 2022 ). In Pakistan, various surveys indicate that raw milk from peri-urban dairy farms is heavily contaminated with AFM 1 and more than 90% of samples may exceed the CODEX maximum tolerable level of 500 ng/l ( Muhammad et al, 2010 ; Yunus et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the recently published literature, it may be generalized that more than 50% raw milk samples in major Pakistani cities exceed the 500 ng/l limit ( Aslam et al, 2016 ; Asghar et al, 2018 ; Akbar et al, 2019 ; Yunus et al, 2019 ). However, processed milk has lower AFM 1 levels than raw milk and has been found to generally comply with the 500 ng AFM 1 /L limit ( Yunus et al, 2019 ; Iqbal et al, 2022 ). Further, the AFM 1 contamination increases in winter ( Hussain, 2009 ; Akbar et al, 2019 ; Yunus et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%